O estado da arte das publicações sobre as olimpíadas de ciências no Brasil - Silva, R. C. (2016)
Science Olympics emerged in the countries of Eastern Europe with the interest that they could compose a group of people through their intellectual capabilities auxiliassem, in developing countries and contribute to their economic and professional growth. Worldwide, these Scientific Olympics started from the end of the twentieth century and were well spread with this statement purpose. This study aims to investigate and analyze the academic production expressed in articles, dissertations and theses produced in Brazil from 2000 to 2014, regarding the Olympics in order to study and understand the configuration of this field of education in Brazil. Methodologically, it is assumed the investigation as the type state of the art within the qualitative approach, seeking the research material that is available on the CAPES portal, digital libraries of Brazilian programs of graduate and magazines. The realization of this gender studies, and seek to identify and analyze the issues usually raised in type studies state of the art in education aims to understand what has been researching this area as a basic requirement for a better understanding of educational settings gravitating around this field, given that, since federal funding, the Olympics have become present in the daily life of our country. It also seeks to show that they contribute or not to improve the Brazilian educational system. As search results, include a total of seven articles, six dissertations and thesis, which consists in the research analysis objects. The analysis of these works can be understood that the Olympics can help: as evaluation parameters; as elements of innovation and motivation; for disclosure issues using technology in education. This shows that there is in the academic community of Science in Education area a thought regarding the Scientific Olympics. The observed results indicate the need for further studies that problematize theoretical questions and reflections that they can get from their relationship with the formal education.